Estimating The Economic Burden Of Influenza On The Older Population In Malaysia - Nur Syazana Mad Tahir; Aniza Ismail; Syed Mohamed Aljunid; Aznida Firzah Abdul Aziz; Amirah Azzeri; Ahmed Abdelmajed Alkhodary (Public Library of Science (PLOS), 2024)
Indexed by Scopus/ERA